Rape, Race, and Capital Punishment: An Enduring Cultural Legacy of Lethal Vengeance?. (October 2019) - Cochran, John K.; Marier, Christopher J.; Jennings, Wesley G.; Smith, M. Dwayne; Bjerregaard, Beth; Fogel, Sondra J.
Historical analyses of southern statutes (i.e., Slave Codes, Black Codes, "Jim Crow, " etc.) and their enforcement reveals evidence of an enduring cultural legacy prescribing lethal vengeance to Blacks who violate White sensibilities, especially for Black males accused of sexually assaulting White females. Using a population of official data on capital murder trials in North Carolina (1977–2009), this study examines the degree to which this cultural legacy endures to the present by examining the joint effects of offender's race and rape/sexual assault on the capital sentencing outcomes of capital murder trial involving White female victims. Our findings reveal support for the continuing endurance of this cultural legacy of lethal vengeance.